2018
DOI: 10.1002/acr.23422
|View full text |Cite
|
Sign up to set email alerts
|

Coping Strategies, Psychological Impact, and Support Preferences of Men With Rheumatoid Arthritis: A Multicenter Survey

Abstract: ObjectiveTo investigate the existence and distribution of 2 typologies (termed “factors”) of men with rheumatoid arthritis (RA) identified through our previous Q‐methodology study (n = 30) in a larger sample of men with RA, and whether differences in psychosocial impact or support preferences exist between the 2 factors, and between men and women with RA.MethodsA postal survey was sent to 620 men with RA from 6 rheumatology units across England, and the support preferences section of the survey was given to 23… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 44 publications
3
8
0
Order By: Relevance
“…In our study, enhanced self‐efficacy was associated with female gender. This finding indicates that men and women with arthritis manage and experience their diseases differently, which is also emphasized in several studies (Flurey, Hewlett, & Rodham, ; Flurey et al, , , ; Gruszczynska & Knoll, ). One study (Flurey et al, ) found that men employed fewer and different strategies than women to manage their condition, females have more positive social support, while men are concerned about retaining their masculine identity.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…In our study, enhanced self‐efficacy was associated with female gender. This finding indicates that men and women with arthritis manage and experience their diseases differently, which is also emphasized in several studies (Flurey, Hewlett, & Rodham, ; Flurey et al, , , ; Gruszczynska & Knoll, ). One study (Flurey et al, ) found that men employed fewer and different strategies than women to manage their condition, females have more positive social support, while men are concerned about retaining their masculine identity.…”
Section: Discussionsupporting
confidence: 66%
“…Also, knowing that higher self‐efficacy scores are associated with lesser psychological distress and tiredness, underline that talking to patients about how to balance their activities and energy according to their individual situations (Grønning et al, ) is needed to support patients to become good self‐managers, (Bech et. al, , Chaleshgar‐Kordasiabi, Enjezab, Akhlaghi, & Sabzmakan, ; Dures et al, ; Ostlund, Björk, Thyberg, Valtersson, & Sverker, ) and that men and women may have different needs (Flurey et al, , , , ; Gruszczynska & Knoll, ).…”
Section: Discussionmentioning
confidence: 99%
“…We found 1‐to‐1 discussions with health professionals to be especially popular among participants, which is unsurprising, because this practice reflects usual care. Our result supports previous research (33,34), including results from a UK study using the same support preferences questionnaire (30). However, the questionnaire did not ask participants whether they would like further 1‐to‐1 sessions in addition to usual care, so whether they would prefer more time with their rheumatology health professionals is unclear.…”
Section: Discussionsupporting
confidence: 92%
“…Data on preferences for self‐management and support services were collected using a questionnaire developed in the UK (30), where participants indicated whether or not they would be interested in participating in 30 different forms of self‐management and support services, within 8 overall categories: discussion groups with other people who have IJD, 1‐to‐1 discussions about coping with IJD, question and answer (Q and A) sessions to ask questions about any aspects of IJD, organized talks or lectures, physical activity sessions, educational group sessions, events to increase public understanding of IJD, and online services (30). The questionnaire also contained questions on preferences regarding practical issues in relation to participation in self‐management and support services (30), and preferred timing of support (18).…”
Section: Methodsmentioning
confidence: 99%
“…Some recent studies suggest that coping strategies may contribute to the dissociation between remission and good functional status observed in a sizeable proportion of patients. Patients with effective coping tend to report a less severe functional impairment in RA (23) and in other rheumatic diseases. 24The new remission definitions for DAS28 (14) confirmed in this setting a tendency to have a stronger association with good functional status than the previous ones.…”
Section: Discussionmentioning
confidence: 99%